2000
DOI: 10.4049/jimmunol.165.6.3384
|View full text |Cite
|
Sign up to set email alerts
|

Role of NF-κB in Cytokine Production Induced from Human Airway Epithelial Cells by Rhinovirus Infection

Abstract: Infection of human epithelial cells with human rhinovirus (HRV)-16 induces rapid production of several proinflammatory cytokines, including IL-8, IL-6, and GM-CSF. We evaluated the role of NF-κB in HRV-16-induced IL-8 and IL-6 production by EMSA using oligonucleotides corresponding to the binding sites for NF-κB in the IL-6 and IL-8 gene promoters. Consistent with the rapid induction of mRNA for IL-8 and IL-6, maximal NF-κB binding to both oligonucleotides was detected at 30 min after infection. NF-κB complexe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
87
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 97 publications
(98 citation statements)
references
References 56 publications
9
87
0
2
Order By: Relevance
“…This analysis showed that the upper band was shifted by Abs to both p65 and p50, suggesting it represents the canonical p65-p50 heterodimer, which we have previously reported to be induced in HRV-16-infected cells (31). In contrast, the lower band was shifted only by Abs to p50, suggesting it may represent p50 homodimers.…”
Section: Evaluation Of the Role Of Nf-b In Mek1/2-mediated Modulationmentioning
confidence: 70%
“…This analysis showed that the upper band was shifted by Abs to both p65 and p50, suggesting it represents the canonical p65-p50 heterodimer, which we have previously reported to be induced in HRV-16-infected cells (31). In contrast, the lower band was shifted only by Abs to p50, suggesting it may represent p50 homodimers.…”
Section: Evaluation Of the Role Of Nf-b In Mek1/2-mediated Modulationmentioning
confidence: 70%
“…IL-8 gene regulation requires activation of nuclear factor (NF)-kB [28]. A. fumigatus proteases can induce IL-8 gene expression by transcription mechanisms involving enhanced DNA binding of NF-kB [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about the events initiating RV-induced cytokine expression in airway epithelium. The IL-8 response to RV serotype 16 infection in BEAS-2B human respiratory epithelial cells is inhibited by antibodies to ICAM-1, implying that integrinmediated signal transduction pathways play a role in RVinduced responses (29). On the other hand, in primary bronchial epithelial cells, anti-ICAM-1 attenuates RANTES but not IL-8 secretion (30).…”
Section: Discussionmentioning
confidence: 99%
“…Down-regulation of the RV-induced cytokine response from one of the other RV16 proteins could serve to attenuate the impact of 3C. As noted above, effects of virus attachment (29) and entry (31) could also play a role.…”
Section: Discussionmentioning
confidence: 99%